Production status of Marwari goat in arid zone (Indian Journal of Animal Production and Management, 2018)
Marwari goats are mainly distributed in seven districts of arid western Rajasthan. This goat is a medium  sized and uniformly black coloured animal with shiny light-gray skin. Horns are corkscrew type and animals  have a curly tuft of hair on forehead. The data on body weight and milk yield pertaining to 133 goats were  analysed. The average body weights at birth, 3, 6, 9, 12, 15, 18, 21 and 24 months age were observed to  be 2.24, 8.79, 13.02, 15.76, 18.50, 22.0, 25.1, 26.0 and 28.20 kg respectively. Male animals attained higher  body weights than females and twin born animals gained lower body weight than single born till one year of  age; thereafter the body weight was more or less similar in both single and twin born kids. On an average  23.3 percent twinning was observed in Marwari goats. Marwari goats kidded first time at the average age  of 25.5 months and most of the goats (64%) kidded in between age group of 18 to 27 months. Female  born with twin birth matured faster and kidded at about 2 years of age. The body weight at first kidding of  Marwari goats was more or less similar in both the categories. Twenty one percent Marwari goats were  observed to be elite in the institute’s flock. Elite goats yielded 47% more milk (in 150-d lactation yield) over  flock average. Goats with twin birth had significantly (P
Keywords: Age at first kidding; Kidding interval; Lactation yield and Prolificacy; Marwari goat; Variability